2013
DOI: 10.1097/ta.0b013e318278937b
|View full text |Cite
|
Sign up to set email alerts
|

The ability of computed tomography to diagnose placental abruption in the trauma patient

Abstract: Diagnostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Our results are concordant with that of previous authors, who have demonstrated a high sensitivity of CT in detecting post-traumatic placental abruption (8, 9). A significant rate of false-positive interpretations points to lack of familiarity with the expected appearance of the placenta on contrast-enhanced CT, given its rarely performed in a gravid patient.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are concordant with that of previous authors, who have demonstrated a high sensitivity of CT in detecting post-traumatic placental abruption (8, 9). A significant rate of false-positive interpretations points to lack of familiarity with the expected appearance of the placenta on contrast-enhanced CT, given its rarely performed in a gravid patient.…”
Section: Discussionsupporting
confidence: 93%
“…Major feature of abruption on CECT is placental non-enhancement (8, 9). Larger degrees of placental non-enhancement are associated with greater risk of fetal demise (9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the presence of diagnostic uncertainty of injuries, ultrasound is possible, as is CT if available and clinically indicated. It is generally accepted that the radiation exposure risk of CT is outweighed by the diagnostic benefit 15 16…”
Section: Discussionmentioning
confidence: 99%